2005
DOI: 10.1002/adem.200400145
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Steel Matrix Composite Locally Reinforced with in Situ TiB2 Particulate using Self–Propagating High–Temperature Synthesis Reaction of Ni–Ti–B System During Casting

Abstract: plasma plume. To achieve a columnar porous structure as well as a high growth rate of the thicker pc-ZrO 2 layer, a pulsed 1 kW laser was applied. The irradiation parameters (pulse duration 1 ms, power density 10 5 W/cm 2 ) were chosen such that conventional thermal evaporation without plasma formation occurred. The targets for the ZrO 2 deposition were pressed and sintered from amperite powder (Y 2 O 3 : 7.79 wt%, HfO 2 : 1.84 wt%, SiO 2 : 0.20 wt%, ZrO 2 : remaining).Investigation of Boundary Layer Reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…4(a-e) shows the typical FESEM of the SHS reaction products synthesized by green preforms with a molar ratio of B/Ti = 2.0 with (a) 30, (b) 40, (c) 50, (d) 60 and (e) 70 wt.% Ni, respectively. It can be observed that large amounts of TiB 2 particulates with the morphology of hexagonal-prism have been synthesized as designed, which is accordant with the results of the study of Horlock et al [3] and our previous study [28,29]. The average sizes of normal TiB 2 particulates are nearly the same and about 4-6 m in the products of 30, 40 and 50 wt.% Ni-Ti-B systems.…”
Section: Xrd Analysessupporting
confidence: 90%
“…4(a-e) shows the typical FESEM of the SHS reaction products synthesized by green preforms with a molar ratio of B/Ti = 2.0 with (a) 30, (b) 40, (c) 50, (d) 60 and (e) 70 wt.% Ni, respectively. It can be observed that large amounts of TiB 2 particulates with the morphology of hexagonal-prism have been synthesized as designed, which is accordant with the results of the study of Horlock et al [3] and our previous study [28,29]. The average sizes of normal TiB 2 particulates are nearly the same and about 4-6 m in the products of 30, 40 and 50 wt.% Ni-Ti-B systems.…”
Section: Xrd Analysessupporting
confidence: 90%
“…2 in Ref. 11). Subsequently, the medium carbon steel melt, which composition is measured by an ARL4460 Metals Analyzer and shown in Table 1, prepared by non-oxidation process in a 5 kg medium-frequency induction furnace with a temperature of about 1 600°C was poured into the mold to ignite the SHS reaction of the preforms.…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9] Moreover, the high-volume fraction of reinforcement distributed only in the local region, which is difficult to or even cannot be realized in the monolithic composite fabricated by conventional casting route due to the poor castability, indicates that the locally reinforced composite is a promising type of material for the reason that it offers a virtually unique combination of low cost and high-wear resistance. 10,11) Furthermore, the majority of iron-and steel-based composites focus on using ceramic particulates, i.e. TiB 2 , TiC, VC, Cr 3 C 2 , etc., 4,8,[9][10][11][12][13][14][15][16][17] as the reinforcements, primarily due to their capability of greatly improving the hardness and wear resistance of the materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the combination of self‐propagating high‐temperature synthesis (SHS) and traditional casting routes provides an easy process to produce ceramic particulate reinforced steel matrix composites 1–15 . Among these composites, in situ ceramic particulate locally reinforced steel matrix composite may be one of the most promising composites which can be widely used in the practical application of excellent wear resistance and/or cutting performance with improved toughness such as pistons, brakes rotor, and mining machine, etc 4–10 .…”
Section: Introductionmentioning
confidence: 99%